PENGARUH JENIS GULA DAN KONSENTRASI EKSTRAK THE HIJAU TERHADAP KARAKTERISTIK FISIKOKIMIA, VIABILITAS BAKTERI ASAM LAKTAT, DAN ORGANOLEPTIK YOGURT NON FAT - Taniaji, Suzanna; Kusumawati, Netty; Kuswardhani, Indah (Jurnal Teknologi Pangan dan Gizi, 2016)
Yogurt is a fermented milk product which utilizes two kinds of lactic acid bacteria, Streptococcus thermophillus (ST) dan Lactobacillus bulgaricus (LB). Utilization of another kind of sugar such as isomalt, which has lower amount of calories compared to sucrose, may be used as an alternative sweetener in yogurt product. Addition of green tea extract is expected to act as natural colorant and aroma and flavor enhancer. The research used experimental design of Randomized Block Design (RBD) nested with two factors: the type of sugar and green tea extract concentrastion with 4 replications. The parameters observed are pH acidity, syneresis, total of lactic acid bacteria, and organoleptic properties (preferences of taste, aroma, and color). The data obtained were statistically analyzed by ANOVA test (Analysis of Variance) at α=5% and continued with Duncan’s Multiple Range Test to determine the level of treatment which has significant difference. The selection of the best treatment is done by Effectiveness Index test. The use of different types of sugar have no significant effect on pH, acidity, syneresis, and total lactic acid bacteria (BAL), while the difference in the concentration of green tea extract was significantly different to acidity, syneresis, and total lactic acid bacteria. Differences in the concentration of green tea extract with isomalt resulted in increasing acidity, syneresis, and total lactic acid bacteria. Utilization of sucrose resulted significant difference in 15% green tea extract concentraion. The use of sucrose has higher acceptability compared to isomalt. Taste properties between sugar and isomalt yogurt is significantly different, while aroma and color is insignificant, which isomalt is in 'rather liked' category. 20% concentration of green tea extract is concluded to be the best treatment, with properties of sucrose-utilized yogurt are 4.532 pH, 0.70% acidity, 5.09% syneresis, 9.4605 log cfu/mL Total Plate Count (TPC), while properties of isomalt yogurt are 4.508 pH, 0.81% acidity, 8.44% syneresis, 9.8743 log cfu / mL TPC.